Rastafari in the new millennium: a Rastafari reader - Barnett, Michael A.; Nettleford, Rex M. (Syracuse University Press, 2014)
pt. 1. An assessment of Rastafani in the new millennium -- part 2. The globalization of Rastafari -- part 3. Rastafari ideology, philosophy, and praxis -- part 4. Gender considerations in the Rastafari movement -- part 5. Religious considerations in the Rastafari movement -- part 6. Rastafari and reggae -- part 7. Political dimensions of the Rastafari movement